Development and Functional Testing of BETAPA ANTIK 2.0: An Android-Based Mobile Application for Community Dengue Surveillance and Reporting in North Sumatra, Indonesia - Risnawati Tanjung; Helfi Nolia; Jernita Sinaga; Adristi Wina Damanik; Deli Syaputri; Samuel Marganda H Manalu; Nelson Tanjung (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Dengue fever remains a major public health concern in Indonesia, particularly in tropical regions such as North Sumatra, where Deli Serdang Regency reports persistently high case numbers. Conventional larva surveillance and the 1 House 1 Larva-Monitor movement (G1R1J) still rely on manual, paper-based reporting that is slow, poorly documented, and difficult to coordinate in real time. The initial BETAPA ANTIK 1.0 application supported larva-survey reporting but lacked educational video content and adult mosquito identification tools, limiting its utility for community education and vector surveillance. This study aims to develop and functionally test BETAPA ANTIK 2.0 (Based on Larvae Surveillance and Analysis Technology), an Android-based mobile application, incorporating GPS-based location tracking, digital case reporting, multimedia public education, and an adult-mosquito identification camera. A design-and-development (Research and Development) approach was employed, following the Waterfall software-development life cycle: requirements analysis, system design, implementation, testing, and maintenance. The application was built on the Android platform using Kotlin/Java, and functional verification was conducted through black-box testing of each feature. BETAPA ANTIK 2.0 provides five core modules: GPS enabled geotagging, a digital reporting workflow integrated with WhatsApp and Gmail, video and poster-based educational media, and an adult-mosquito identification camera covering 23 species. All functional (black-box) test cases performed according to specifications, with the only limitation being dependence on a stable internet connection. Usability, user acceptance, and the accuracy of mosquito-identification were not formally evaluated and are identified as priorities for future studies. BETAPA ANTIK 2.0 was successfully developed and passed functional (black-box) testing, representing a promising digital tool to support participatory dengue surveillance and reporting. However, its effectiveness in dengue control requires further filed implementation and usability evaluation. Recommended next steps include developing an offline mode, risk-zone notifications, and integration with existing health information systems. Keywords: Dengue Prevention and control, Mosquito Vectors, Mobile Applications, Epidemiological Surveillance, Community Participation, Indonesia